Geometric evolution of the Horcones Inferior Glacier (Mount Aconcagua, Central Andes) during the 2002-2006 surge - Pitte, Pedro Miguel (2016)
The Central Andes of Chile and Argentina (31-35ï¿S) contain a large number and variety of ice masses, but only two surging glaciers have been studied in this region. We analyzed the 2002-2006 surge of the Horcones Inferior Glacier, Mount Aconcagua, Argentina, based on medium spatial resolution (15-30 m) satellite images and digital elevation models. During the buildup phase the glacier was stagnant, with velocities lower than 0.1 m/d. In the active-phase velocities reached 14 m/d and the glacier front advanced 3.1 km. At the peak of the active phase (2003-2004), the area-averaged elevation change was-42 m in the reservoir zone (2.53 km2) and +30 m in the receiving zone (3.31 km2). The estimated ice flux through a cross section located at 4175 meter above sea level was 108 m3 during a period of 391 days, a flux that suggests a mean glacier thickness at this location of ~90 m. The depletion phase showed a recovery of the reservoir zone elevation, the down wasting of the receiving zone (-17 m, 2007-2014), and a return to quiescent velocities. The short active phase, the abrupt change in the velocities, and the high level of the proglacial stream indicate a hydrological switch (Alaska type) trigger. The 2002-2006 and 1984-1990 surges of Horcones Inferior were synchronous with the surges of nearby Grande del Nevado Glacier. These events occurred after periods of positive mass balance, so we hypothesize a climate driver.